Headache - Begasse de Dhaem, Olivia; Bernstein, Carolyn (New York, NY : Oxford University Press, 2023)
Presents clinical scenarios exploring headache medicine and treatments. Headache Medicine is a complex and constantly developing field, often relying on outdated and time-intensive textbooks. The purpose of this book is to educate readers on the diagnosis and management of commonly encountered headache disorders through brief discussion of relevant and specific cases.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 5, 2023).
Keywords: Headache -- Diagnosis; Headache -- Treatment; Health and Wellbeing; Clinical & internal medicine